2020
DOI: 10.1111/jnc.15127
|View full text |Cite
|
Sign up to set email alerts
|

Endomorphin analog exhibited superiority in alleviating neuropathic hyperalgesia via weak activation of NMDA receptors

Abstract: Morphine is a key drug for the treatment of pain but its side effects limit its clinical application. MEL-0614, an endomorphin-1 analog, has fewer side effects than morphine in addition to its powerful analgesic effect. In this study, we measured the effect of morphine and MEL-0614 on hyperalgesia (7 days) and neuropathic allodynia (14 days) after thermal, mechanical, and cold stimulation. We found that after four and eight consecutive days of intrathecal administration (1, 3, and 10 nmol), morphine induced se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…Numerous studies have shown that the activation of microglia has a crucial role in the increase of pain, especially in terms of opioid-induced tolerance and hyperalgesia, , which fully indicated that the mechanisms of tolerance and hyperalgesia development may share many similarities. In our previous study, we found that MEL-0614 induced less hyperalgesia and had an alleviation effect on morphine-induced hyperalgesia in neuropathic pain . We further investigated whether repeated administration of morphine or MEL-0614 would induce the development of tolerance in CPSP.…”
Section: Discussionsupporting
confidence: 90%
“…Numerous studies have shown that the activation of microglia has a crucial role in the increase of pain, especially in terms of opioid-induced tolerance and hyperalgesia, , which fully indicated that the mechanisms of tolerance and hyperalgesia development may share many similarities. In our previous study, we found that MEL-0614 induced less hyperalgesia and had an alleviation effect on morphine-induced hyperalgesia in neuropathic pain . We further investigated whether repeated administration of morphine or MEL-0614 would induce the development of tolerance in CPSP.…”
Section: Discussionsupporting
confidence: 90%
“…During the operation, a heating blanket was used to keep the body temperature stable, and all operators skillfully performed the related surgical procedures to shorten the operation time. With reference to previous studies [ 29 , 30 ], sodium pentobarbital was prepared as a solution with a final concentration of 5 mg/ml to avoid irritation. After surgery, wounds were topically disinfected with 75% ( v / v ) ethanol, but not with systemic antibiotics, to avoid interference with experimental pharmacological treatments.…”
Section: Methodsmentioning
confidence: 99%
“…bone cancer pain, HO-1, neuroinflammation, NF-κB, Nrf2, nuclear translocation chose the best experimental scheme and reduced the number of animals as much as possible. Referring to the previous literature (Fulas et al, 2020;Hu et al, 2017;Ma et al, 2020), sodium pentobarbital was used to anaesthetize rats. Sodium pentobarbital was finally configured to a final concentration of 5 mg/ml solution to avoid irritation.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…The behavioural experiments were 6 rats per group (Ni et al, 2019), 4 rats per group for western blot (He et al, 2020) and immunofluorescence (Ni et al, 2020), 5 rats per group for real-time quantitative PCR (Mohamed et al, 2020) and enzyme-linked immunosorbent assay (Zhang et al, 2019) and 10 rats per group for computed tomography (CT) reconstruction and histological analysis of bone (Xu et al, 2019). Referring to the previous literature (Ma et al, 2020), the animals were simply randomly grouped. For example, in the Figure 1a, 52 rats were artificially numbered 1-52, and then each rat corresponded to a pseudorandom number generated by computer software on the order of 1-52.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation